2024
DOI: 10.1038/s41467-024-45516-4
|View full text |Cite
|
Sign up to set email alerts
|

A nonmetallic plasmonic catalyst for photothermal CO2 flow conversion with high activity, selectivity and durability

Xueying Wan,
Yifan Li,
Yihong Chen
et al.

Abstract: The meticulous design of active sites and light absorbers holds the key to the development of high-performance photothermal catalysts for CO2 hydrogenation. Here, we report a nonmetallic plasmonic catalyst of Mo2N/MoO2-x nanosheets by integrating a localized surface plasmon resonance effect with two distinct types of active sites for CO2 hydrogenation. Leveraging the synergism of dual active sites, H2 and CO2 molecules can be simultaneously adsorbed and activated on N atom and O vacancy, respectively. Meanwhil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…The CO molecule is a valuable compound for the synthesis of a large number of different chemicals . Particularly, the RWGS is a key step in obtaining C1 and C2+ products. , As the main result, this work uncovers new, highly active, selective, and stable indium-based species and provides a structure–activity relationship rationalizing the functional properties.…”
Section: Introductionmentioning
confidence: 91%
“…The CO molecule is a valuable compound for the synthesis of a large number of different chemicals . Particularly, the RWGS is a key step in obtaining C1 and C2+ products. , As the main result, this work uncovers new, highly active, selective, and stable indium-based species and provides a structure–activity relationship rationalizing the functional properties.…”
Section: Introductionmentioning
confidence: 91%
“…Minimizing the catalyst size to clusters or even single atoms (SAs) maximizes the exposure of active sites, which contributes to boosting the catalytic activity. SA catalysts exhibit high catalytic activity in photothermal catalysis due to the atomically dispersed nature of the metal sites. , Co SA catalysts, among various inexpensive metals, have demonstrated their competitiveness as candidates for facilitating hydrogen production. , A Co SA exhibits a low Gibbs free energy of hydrogen production, which plays a vital role in H 2 O dissociation. , Doping the catalyst with an appropriate amount of Co SA can effectively adjust the d-band center and enhance the absorption of visible light. Studies have shown that in the condition of doping semiconductor materials, although the bandgap state excited by visible light can enhance visible light absorption, the carriers in the bulk phase tend to recombine via the bandgap state, leading to reduced photogenerated charge separation efficiency, , whereas, in the case of SA catalysts loaded on the metal oxide surface, the generated charge carriers can directly interact with adsorbed molecules to facilitate effective utilization. , In the CO 2 reduction process, the transition metal Ni can efficiently convert NIR light into hot electrons and thermal energy through the localized surface plasmon resonance (LSPR) effect, which leads to rapid heating of the local interface, induces a strong hot spot effect, and promotes the CO 2 activation process. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, local heating of the catalyst created by photothermal effects can provide effective photothermal conversion to a higher charge separation/transfer efficiency. 22,23 However, not all electric effects play a facilitating role in photocatalysis, such as the exciton effect, which may inhibit the photocatalytic performance. After absorbing the photon energy, the photogenerated electron–hole pair assumed a bound state under coulombic interactions, which reduced the number of free active charges.…”
Section: Introductionmentioning
confidence: 99%